Analisis Performa Jaringan 4G LTE Telkomsel di Tinombo Kabupaten Parigi Moutong Sulawesi Tengah - Fachrozi Haykal Nugraha; Dikky Chandra; Muhammad Putra Pamungkas (SM Institute, 2025)
The development of communication technology, especially 4G LTE, has driven an increase in the need for high-speed internet services in all regions, including rural areas such as Tinombo District, Parigi Moutong Regency, Central Sulawesi. However, geographical conditions dominated by hills and bays cause the quality of Telkomsel's 4G LTE network in this region to vary and is not fully optimal. This study aims to analyze the performance of Telkomsel's 4G LTE network in Tinombo based on Key Performance Indicator (KPI) parameters which include Reference Signal Received Power (RSRP), Reference Signal Received Quality (RSRQ), and Signal to Interference and Noise Ratio (SINR). The method used is a drive test with the G-NetTrack Pro application on mobile devices, covering field measurements from Tinombo Village to Sipayo Village, Sidoan District. Data is obtained through real-time signal recording configuration, with support for routing and location of Base Transceiver Station (BTS) using Google Earth Pro and Cell Mapper. The analysis was conducted to evaluate the signal strength, signal quality, and interference level on Telkomsel's 4G LTE network. The results of the study are expected to provide scientific information related to the actual condition of 4G LTE network performance in rural areas, as well as become a reference for service providers in optimizing network quality. This research is also relevant for academics, researchers, and telecommunication practitioners, especially in the field of Radio Frequency Engineering, in understanding the technical challenges of network implementation in areas with complex topography.